ENVIRONMENTAL AND SOCIAL IMPACT ANALYSIS USING REMOTE SENSING: CASE STUDY OF FOOD ESTATE MERAUKE, PAPUA - Batjo, Athanaya; Ayunita, Elia; Kharisma (MAJALAH PEMBELAJARAN GEOGRAFI, 2025)
This study aims to analyze the impact of the implementation of the Food Estate project on environmental sustainability in Merauke Regency, Papua, using remote sensing data (NDVI and MNDWI) along with spatial analysis. From 2016 to 2020, before the project was implemented, the area was largely covered by healthy vegetation and natural ecosystems that helped maintain ecological and hydrological balance. However, since the program started in 2021 up to 2024, there has been a noticeable reduction in green vegetation, suggesting extensive land conversion and environmental stress. NDVI and MNDWI results point to declining soil quality and disruptions in the natural water cycle, which raise concerns about possible droughts and seasonal floods. The spatial analysis also shows that some Food Estate areas overlap with protected zones and indigenous territories, which could lead to land use conflicts and increase social inequality. These findings suggest that the project may be threatening local ecosystems and the livelihoods of communities who depend on them. Therefore, further policy evaluation and the implementation of conservation techniques and sustainable environmental management are needed to ensure that the project meets food security goals without sacrificing ecosystem sustainability and indigenous rights.